2021
DOI: 10.3390/en14010186
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hole Arrangement and Density Ratio on the Heat Transfer Coefficient Augmentation of Fan-Shaped Film Cooling Holes

Abstract: An experimental study was performed to investigate the effects of the arrangement of fan-shaped film cooling holes and density ratio (DR) on heat transfer coefficient augmentation. Both single- and multi-row fan-shaped film cooling holes were considered. For the multi-row fan-shaped holes, the heat transfer coefficient was measured at DRs of 1 and 2, and both staggered and inline arrangements of holes were considered. For the single-row fan-shaped holes, DR = 1.0, 1.5, 2.0, and 2.5 and M = 1.0 and 2.0 conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Lenzi et al [12] revealed the unsteady flowfield characterization of a shaped-hole effusion system in the swirling mainstream from detailed experimental tests. Kim et al [13] investigated the influence of fan-shaped hole position and jet-to-crossflow density ratio on the film cooling performance. Baek et al [14] performed a numerical study to deeply reveal the inherent flow dynamics of fan-shaped hole film cooling by using the large eddy simulation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Lenzi et al [12] revealed the unsteady flowfield characterization of a shaped-hole effusion system in the swirling mainstream from detailed experimental tests. Kim et al [13] investigated the influence of fan-shaped hole position and jet-to-crossflow density ratio on the film cooling performance. Baek et al [14] performed a numerical study to deeply reveal the inherent flow dynamics of fan-shaped hole film cooling by using the large eddy simulation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…This so-called film cooling technology has been widely used for decades in turbomachinery for its high reliability in turbine blade cooling. Numerous studies have been carried out to reveal the mechanism of film cooling, optimize the design of hole, and improve cooling efficiency [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the film cooling effectiveness of the forward expansion hole was higher. Kim et al, 2021 performed an experimental study to investigate the effects of the arrangement of fan-shaped film cooling holes and the density ratio on the heat transfer coefficient and found that, for the given fan-shaped hole parameters, the effects of the row-to-row distance and hole arrangement were not significant. Burd et al, 1998 used hot-wire anemometry measurements to measure the average velocity and turbulence intensity of the mixing area of the coolant and free-stream flows in film cooling and found that under low free-stream turbulence conditions, pronounced differences existed in the flow field between L/D 7.0 and 2.3.…”
Section: Introductionmentioning
confidence: 99%